Relationship of acid–base imbalance with hemorrhage volume and mortality in intracerebral stroke hemorrhage - Gavin Mukti; Iwan Setiawan; Metana Puspitasari; Sulistyani Sulistyani (Universitas 'Aisyiyah Yogyakarta, 2026)
This study aimed to evaluate the relationship between acid-base balance disturbances and intracerebral hemorrhage volume with mortality rates in hemorrhagic stroke cases. The research used an observational analytic design with a cross-sectional approach and was conducted at Dr. Soeratno Gemolong General Hospital, Sragen, from September to November 2024. The study population consisted of medical records of patients diagnosed with hemorrhagic stroke at the hospital between August 2021 and August 2024 who met the inclusion criteria. A total of 50 samples were selected using a purposive sampling technique. Data analysis included univariate analysis, bivariate analysis using the Chi-Square test, and multivariate analysis using logistic regression. The results showed a significant relationship between acid–base balance disturbances and intracerebral hemorrhage volume with mortality in hemorrhagic stroke cases (p=0.001). In addition, intracerebral hemorrhage volume was significantly associated with mortality (p=0.007). Multivariate analysis confirmed that both acid–base imbalance and hemorrhage volume significantly influence mortality outcomes. These findings indicate that acid–base imbalance and intracerebral hemorrhage volume greater than 30 ml are strong predictors of mortality in hemorrhagic stroke patients. Therefore, strict monitoring of arterial blood gases, neurological status, and hemodynamic stability is essential during the acute phase of care. Early detection of physiological deterioration and prompt intervention may help reduce the risk of adverse outcomes. Future research is recommended to use prospective multicenter designs with larger sample sizes to further clarify causal relationships and evaluate whether early correction of acid–base disturbances can improve mortality outcomes in hemorrhagic stroke patients.